1982-1983 ネン マクマードサウンド チイキ ノ コクサイ キョウドウ カンソク ホウコク - 神沼, 克伊; カミヌマ, カツタダ; Kaminuma, Katsutada (1983)
P(論文) 1982-1983年のマクマードサウンド地域の国際共同観測は, 第3年目を迎えた「エレバス火山国際地震研究(IMESS)」を実施した。日本からは神沼克伊(国立極地研究所), 植木貞人(東北大学), 小山悦郎(東京大学地震研究所)の3名が参加した。日本隊はテレメータ観測網の記録系の保守, 観測した磁気テープの再生, 読み取りを担当しているが, 1982年10月8-9日には, 大きな群発地震が発生したことをつきとめた。その他, 日本隊だけで山腹に9点の地震計を設置し, 臨時観測を約50日間実施した。また, 山頂, 山腹, 合計30点で重力測定も実施した。 Three Japanese scientists visited McMurdo Station from November 4,1982 to January 13,1983 to participate in the International Mt. Erebus Seismo-logical Studies (IMESS). This was the third year of the cooperation project among Japan, the United States and New Zealand. The members are K. KAMINUMA (National Institute of Polar Research), S. UEKI (Faculty of Science, Tohoku University) and E. KOYAMA (Earthquake Research Institute, the University of Tokyo). Following research programs were carried out : 1) Seismic observation by the telemetry network; Japanese scientists played back the magnetic tapes which have been recorded since September 1982. The daily frequencies of volcanic earthquakes occurring in and around Mt. Erebus were counted and earthquakes were scaled. 2) Observations by a temporary seismic network; From November 15,1982 to January 4,1983,nine seismic temporary station were established on the flank of Mt. Erebus for determining the earthquake locations with high accurately. 3) Gravity measurements; LaCoste-Romberg gravimeter model G were used at nine temporary seismic stations. Twenty additional gravity stations were also established around the summit crater of Mt. Erebus. departmental bulletin paper